Profile of avascular necrosis cases among kidney transplant recipients on a lowdose steroid regimen, A Retrospective Study - Muhammad Tassaduq Khan,; Sidrah Rashid,; Rashid Bin Hamid,; Naranjan Lal,; Sabahat Sarfaraz,; Syed Hasan Farooq, (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the clinical profile, biochemical parameters and outcomes of kidney transplant recipients who developed avascular necrosis while on a low-dose steroid regimen. Method: The descriptive, retrospective cross-sectional study was conducted from January to December 2022 at the Renal Transplant Unit of the Dow University of Health Sciences, Karachi, and comprised data on kidney transplant recipients diagnosed with avascular necrosis between March 2017 and December 2022. Data on demographics, biochemical markers, steroid protocols, joint involvement, diagnostic techniques, rejection episodes and surgical interventions was collected. Data was analysed using SPSS 27. Results: Of the 30 patients, 21(70%) were males and 9(30%) were females. The overall mean age was 37.23±8.62 years (range: 24-60 years). Avascular necrosis diagnosis was confirmed by magnetic resonance imaging scan in 28(93.3%) cases. Surgical intervention was required in 8(26.7%) patients. Rejection episodes were 16(53.3%) in the first six months, while 14(46.7%) developed avascular necrosis without prior rejection (p=0.689). A significant correlation was observed between gender and surgical intervention, with females more likely to require surgery compared to males (p=0.032). Conclusion: Female patients showed a higher likelihood of requiring surgical management, highlighting the importance of gender-sensitive orthopaedic monitoring post-transplant. Key Word: Avascular necrosis, Kidney transplant, Low-dose steroid, Surgical intervention, Orthopaedic outcomes.